A case of traumatic neuroma of the lower lip - HAMASAKI, Ken; SATO, Yuho; SUZUKI, Kumiko; KUDOU, Masanori; ARAI, Hiroyuki; ISHII, Yoshimasa (Japanese Journal of Oral and Maxillofacial Surgery, 2008)
Traumatic neuroma is a hyperplastic lesion caused by the superfluous regeneration of nerve cells at acut surface. We report a case of traumatic neuroma arising in the lower lip of a 7-year-old boy. The patient wasinvolved in a traffic accident in May 2003, causing a bone fracture of the femoral region and laceration of the lowerlip. The lower lip was sutured surgically. Shortly after treatment, the patient noticed a swelling in the right side ofhis lower lip and consulted our clinic for a detailed examination on January 7, 2004. Macroscopically, an elasticand hemispheric painless soft mass with a diameter of 1.0cm was noticed at the suture line. Under a clinical diagnosisof mucocele, we performed enucleation of the tumor. Histologically, irregular proliferation of the peripheralnerve cells and nodular formation of Schwann cells were observed. The tumor was diagnosed to be a traumaticneuroma. During 2 years of postoperative follow-up, the patient has had no evidence of recurrence.